2008
DOI: 10.1038/eye.2008.315
|View full text |Cite
|
Sign up to set email alerts
|

Lens thickness of Indian eyes: impact of isolated lens opacity, age, axial length, and influence on anterior chamber depth

Abstract: Purpose To report relationship of age group and axial length (AL) category to lens thickness values in eyes with a clear lens or different types of isolated cataract (nuclear, cortical, and posterior subcapsular (PSC)). Further, we evaluated lens thickness values on anterior chamber depth (ACD) in these eyes. Design Observational clinic-based study. Methods An observational study of 1442 eyes of 1442 individuals (816 eyes with isolated cataract and 626 eyes with clear lens) of those above 25 years of age was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 19 publications
(37 reference statements)
6
33
0
2
Order By: Relevance
“…The close correlation between LV and ACV found this time was in accordance with these. Praveen et al [26] reported that the lens thickness increased markedly in subjects aged 41–50 years, and this might account for the greater reductions in ACV and ACD in subjects aged 41–50 years in our study. A decrease in ACW with age was also found in our study.…”
Section: Discussionmentioning
confidence: 47%
“…The close correlation between LV and ACV found this time was in accordance with these. Praveen et al [26] reported that the lens thickness increased markedly in subjects aged 41–50 years, and this might account for the greater reductions in ACV and ACD in subjects aged 41–50 years in our study. A decrease in ACW with age was also found in our study.…”
Section: Discussionmentioning
confidence: 47%
“…The increase in LT with age can be attributed to the increase in protein fiber layers forming under the capsule. As mentioned, the ACD decreases with age, and in this regard, the increase in LT can be the main cause for the decrease in ACD, and this has been stated in the report by Praveen et al [29]. …”
Section: Discussionmentioning
confidence: 81%
“…The risk of nuclear cataracts increases with the amount and duration of smoking, adding confidence to the existence of a causal relationship between smoking and nuclear opacities. Two studies from diverse ethnic groups identified larger lens size as a risk factor for nuclear cataracts [15,16] . Longitudinal studies showed that having a larger lens conferred increased risk of developing nuclear opacities over a 5-year follow-up period [17] .…”
Section: Different Risk Factors For Each Type Of Age-related Cataractsmentioning
confidence: 99%
“…As with nuclear cataracts, lens size was identified as a significant risk factor for cortical cataracts. However, unlike nuclear cataracts, the increased prevalence and incidence of cortical opacities were linked to having a smaller, not a larger lens [15][16][17]31] . Several studies have shown that diabetics also have an increased risk of developing cortical cataracts and PSCs, although diabetics with well-controlled blood sugar develop a similar spectrum of age-related cataracts as nondiabetics [32,33] .…”
Section: Different Risk Factors For Each Type Of Age-related Cataractsmentioning
confidence: 99%